LAND USE IMPACT ON SOIL HYDROLOGY AND NUTRIENT STATUS IN A TYPICAL KARST ENVIRONMENT - Wang, Xiaojun; Yifan , Zhang (International Journal of Renewable Energy and Environmental Sustainability (IJREES), 2023)
In karst landscapes, water availability profoundly influences ecosystem management and restoration. The hydrological function of soil is pivotal in these regions, where water is often a limiting factor. Recent attention has been directed towards optimizing water and soil resources in the restoration of karst rocky desertification areas. Various factors, including land use types, management practices, and cultivation methods, exert a notable influence on soil hydrological properties. Studies, such as those by Yang and colleagues in Guangxi's Huangjiang area, have underscored the significant impact of diverse vegetation cover types on these properties. Additionally, the stoichiometric characteristics of soil carbon (C), nitrogen (N), and phosphorus (P) play a vital role in predicting soil nutrient saturation status. While extensive research has examined the ecological stoichiometry of C, N, and P in karst regions, particularly in relation to vegetation and litter, limited attention has been given to the correlation between soil hydrological properties and these key elements under different land use types. Moreover, the mechanisms governing their spatial effects remain elusive. This chapter seeks to bridge this gap by exploring these correlations, thereby furnishing a theoretical framework for comprehending the intricate soil-water-fertilizer coupling mechanism in karst regions.